Género y gestión del riesgo de desastres: análisis comparado de la agenda internacional y latinoamericana y caribeña - Ana Gabriela Fernández-Saavedra; Rosario González-Arias; Sandra Dema-Moreno (Revista Iberoamericana de Estudios de Desarrollo)
The article carries out a comparative documentary analysis in a double sense: on the one hand, on the incorporation of the gender perspective in the main multilateral agreements on disaster risk reduction approved in the international, Latin American, and Caribbean sphere and, on the other, on the treatment of disasters risk reduction in the equality agenda in the same territorial area. The results show that there has been an accelerated process of incorporating the gender perspective in disaster risk management on a global scale, but not in Latin America and the Caribbean, a geographical context in which said evolution has not been homogeneous or constant. The lag identified in this region, especially affected by disasters, reveals the importance of having a harmonized regulation, which also incorporates the scientific evidence obtained on the matter in recent decades.